Faktor Personal Hygiene Penjamah dan Kondisi Sanitasi TPM Terhadap Kualitas Bakteriologis Makanan Jajanan di Kuliner Pasar Cidu Kota Makassar - Zaenab, Zaenab; Nurhaidah, Nurhaidah; Chalizhah, Izhiq; Azizah, Nurfitriani (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2024)
The most popular snack culinary center in the city of Makassar currently is Pasar Cidu Culinary in Makassar City. However, food and drink snacks sold by street vendors do not apply hygiene and sanitation factors in the processing process, which can cause biological contamination which can cause digestive problems in the community. This research aims to determine the relationship between the personal hygiene of handlers and the bacteriological quality of germ numbers in snacks at Pasar Cidu Culinary, Makassar City. Using an analytical observational method with a cross-sectional approach, this research involved 20 snack samples and 20 respondents selected by purposive sampling. Handlers' personal hygiene data was obtained through direct observation based on questionnaires, while data on the number of germs was obtained through ALT examination, and analyzed using Fisher's correlation. The research results showed that 95% of respondents had poor personal hygiene and 19 samples did not meet the requirements based on BPOM Regulation No. 13 of 2019, the maximum limit for germ numbers in processed meat foods is 104 colonies/g and fruit juice drinks are 10 colonies/ml. Statistical tests show that there is a relationship between the personal hygiene of the handler and the bacteriological quality of the snacks with a p value = 0.050. The conclusion of this research is that the personal hygiene of handlers is related to the bacteriological quality of germ numbers in snacks at Pasar Cidu Culinary. For this reason, it is hoped that traders can improve personal hygiene practices such as keeping their hands and nails clean and using PPE such as hand aprons and head coverings.